Study of Antimicrobial Property of Spices in Starch Films: An Experimental Proposal - Maciel, Cristiane C. [UNESP]; Rodrigues, Jessica S. [UNESP]; Freitas, Amanda S. M. de [UNESP]; Ferreira, Marystela [UNESP] (Brazilian Chemical Soc, 2020)
The proposed experiment studies the antimicrobial properties of spices, cloves and cinnamon. Materials of easy access and low cost were used, aiming that the experimental procedure can be applied in laboratory classes of undergraduate courses. In this context, corn starch films were produced with infusions of spices. To facilitate the handling of the film, a plasticizer, glycerol, was added. The films were prepared from solutions and dried at room temperature. The visual analysis, documented by photos, was performed daily for 7 days. The visual comparison of the films was performed with the control (without spices), cloves and cinnamon within the expiration date, and with the same expired spices. The total duration of the experiment was one week, with the preparation of the films made in the first class, followed by the daily monitoring of the samples and the closing of the experiment in the next week's class. It was possible to observe the gradual growth of microorganisms in the control films and those prepared with extracts of cloves and cinnamon out of date. While for films prepared with cloves and cinnamon within the current validity period, microbial formations were not observed.
Keywords: Clove; cinnamon; starch thermoplastic; antimicrobial properties; teaching experiment